Initial aortic repair versus medical therapy for early uncomplicated type B dissections - Jyh Shinn Teh; Jui-Hsiang Chen; Ying-Ting Kuo; Chun-Yang Huang; Tai-Wei Chen; Chun-Che Shih; Chiao-Po Hsu (PLoS ONE, 2025)
Background Uncomplicated type B aortic dissections was regarded benign and treated with optimal medical therapy (OMT). However, studies showed highly unpredictable of disease progression, which suggested the need of earlier intervention. To search for features associated with worse outcomes with OMT is important due to risk of intervention. We investigated mortality and aortic remodeling between aggressive (OMT and pre-emptive endovascular intervention) and conservative therapy (OMT and necessary operations). Methods Retrospective analysis was performed in acute and subacute uncomplicated type B dissections patients, including typical aortic dissection, intramural hematoma and penetrating atherosclerotic ulcer, diagnosed between June 2005 and May 2021. Patients with Marfan, traumatic, iatrogenic, zone 0 (ascending aorta) involvement, and maximal aortic diameter > 45mm were excluded. Patients are classified according to initial management. Results 77 and 33 patients in the aggressive and conservative groups were included respectively. There was no differences in baseline clinical and radiological characteristics between them. During mid-term follow-up (median 62.5 months), there was no difference in the mortality but the incidence of 30-day acute kidney injury was significantly higher in aggressive group. Positive aortic remodeling was noted in aggressive group, with development to complete or incomplete false lumen thrombosis (p < 0.01). Conclusion Aggressive pre-emptive endovascular therapy though has acceptable outcomes and positive aortic remodelling in early uncomplicated type B dissection with maximal aortic diameter ≤ 45mm. However, it could not translate into better mid-term survival than conservative therapy, but with higher risk of 30-day acute kidney injury. Aggressive pre-emptive endovascular intervention should be cautious in these patients.